IDENTIFIKASI JENTIK NYAMUK Aedes aegypti PADA BAK MANDI DI TOILET KAMPUS V UNIVERSITAS INDONESIA TIMUR - Nardin Nardin; Nurwahidah Fa’al Santri; Riskhi Ashafil (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
This research was motivated by the high incidence of mosquito-borne diseases, especially Aedes aegypti. This study aims to identify the larvae of Aedes aegypti mosquitoes in the bath in the toilet on campus V of the University of East Indonesia Makassar. This research is descriptive, the population in this study is all water in the bath from 15 toilets on campus V of the University of East Indonesia Makassar. The sample used is 5 samples of bathtub water. From the results of the study it can be concluded that there is no larva of Aedes aegypti in the bath in the toilet campus V University of East Indonesia Makassar